A Web-Based Facility Allocation System With Google Maps Integration. A Case Study of Uganda Christian University Bishop Barham University College Kabale - Laban Mugisha (Uganda Christian University, 2024)
This research endeavors to address the challenges of campus navigation and resource allocation at Bishop Barham University College (BBUC) in Kabale, Uganda, through the development and implementation of a Web-Based Facility Allocation System with Google Maps Integration. The historical evolution of campus management systems, contextual challenges unique to BBUC, and theoretical frameworks guiding the research are explored. The study identifies the absence of a dedicated system tailored to BBUC's needs, hindering effective access and management of facilities. The main objective is to enhance campus management by developing a system that optimizes facility allocation and navigation. A mixed-methods approach is employed, combining quantitative and qualitative methodologies to gather comprehensive data. Surveys, interviews, and observations are used to collect data from stakeholders. The research design includes a quasi-experimental pre-test and post-test evaluation to measure system effectiveness. Rigorous testing phases ensure functionality, usability, and integration with Google Maps. Ethical considerations, limitations, and the significance of the study are discussed. The results of the research aim to inform the design, development, and implementation of the proposed system, ultimately improving campus management and user satisfaction at BBUC.
This project was to address specific needs at Bishop Barham University College (BBUC) in Kabale, Uganda, by tackling gaps in campus navigation and resource allocation. Through the integration of Google Maps, the developed system provided real-time guidance and accessible information about campus facilities. The study highlighted the importance of customized campus management solutions, particularly for institutions with unique spatial layouts and operational challenges like BBUC. This system enhanced the user experience for students, staff, and visitors, and it also serves as a scalable model that could be adapted by other institutions facing similar challenges.
Keywords: Campus Navigation; Resource Allocation; Web-Based System; Google Maps Integration